Time and The Diary in Captivity, a Case Study: The Diary of Fela Szeps (1942-1944) - Batsheva Ben-Amos (European Journal of Life Writing)
When the diarist is free from imminent danger, and has reasonable flexibility in managing a daily routine, clock-and-calendar time helps in organizing the individual’s chosen social roles and responsibilities as well as their private interests, all of which are the building blocks of personal identity. Daily objective time is not bestowed as such with a symbolic meaning but is taken for granted as a point of reference.